Industrial revolution 4.0 and the development of accounting information system: an imaginary dialogue - Ganis Sukoharsono, Eko (International Journal of Engineering and Technology, 2020)
The paper is an imaginary dialogue on industrial revolution 4.0 (IR4.0) and the development of accounting information system. It explicates a thought of changing on accounting information system in the era of industry 4.0. The imaginary dialogue is between Accountant and Industrialist, both are concerned on the movement of industry 4.0 and accounting information system approach. Its aim is to explore the connection between IR4.0 and the development of AIS. IR4.0 characterized by Interoperability, Virtualization, Decentralization, Real Time Capability, Service Orientation, and Modularity significantly contributes the accuracy and timeliness of accounting information and the quality of AIS.Â Â